SOSIALISASI STRATEGI PENCEGAHAN DAN PENANGGULANGAN STUNTING: PROGRAM PENGABDIAN MASYARAKAT DI DESA GOLO KANTAR KECEMATAN BORONG KABUPATEN MANGGARAI TIMUR - manti, frederikus; Pena, Veronika Ruba; Budiman, Oktavianus (Merwinspy Publisher, 2025)
This article discusses a community service program in the form of socialization to the community, particularly for pregnant women and nursing mothers, on how to prevent and overcome stunting, which requires special attention in rural areas such as Golo Kantar village. This community service program aims to increase the knowledge of the Golo Kantar Village community through socialization of stunting prevention and control strategies. The implementation method includes a needs survey, planning of socialization materials, logistical preparation, implementation of interactive socialization activities, and evaluation of program impact. The results of this activity are expected to increase public awareness and knowledge in overcoming stunting in their families so that it is hoped that the stunting rate can slowly decrease.